DOKTRIN PREDESTONASI JHON CALVIN: Perspektif Teologis dan Implikasinya bagi Pemahaman Keselamatan - Resti Resti; Bilda Tallo, Viorentika Ranak, Delvi Kendenan, Apriliani Irens (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study examines John Calvin's doctrine of predestination, focusing on its theological perspective and implications for the understanding of salvation. Calvin's doctrine asserts that God has predetermined since eternity who will be saved and who will be damned, based on an absolute divine will that is independent of human effort. This research explores how this doctrine shapes the concept of salvation in Calvinist theology, providing comfort to believers through the assurance of salvation, while also sparking debate about the justice and love of God. By analyzing key theological arguments and responses to criticisms, this study aims to offer deep insights into the impact of the doctrine of predestination within Christian theology and its relevance to contemporary faith practices.